2022
DOI: 10.1177/10963480221087964
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Wellbeing: Re-Thinking Hedonic and Eudaimonic Dimensions

Abstract: Research on tourists’ eudaimonic and hedonic wellbeing has grown exponentially in the tourism literature. The paper re-examines the conceptualization of psychological tourist wellbeing. While there is agreement that tourist wellbeing is multidimensional in nature, it is unclear what specific dimensions, or psychological domains, underpin tourists’ hedonic and eudaimonic wellbeing. Models that summarize these domains seemingly overlap, notably the PERMA and DRAMMA models. Ideas on re-conceptualizing tourist wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…At the same time, food can be a key element in creating wellness experiences characterized as a hedonic rather than eudaimonic feature (Filep et al. , 2022; Ahn et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, food can be a key element in creating wellness experiences characterized as a hedonic rather than eudaimonic feature (Filep et al. , 2022; Ahn et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…At the same time, food can be a key element in creating wellness experiences characterized as a hedonic rather than eudaimonic feature (Filep et al, 2022;Ahn et al, 2019;Voigt et al, 2010). According to the hedonic model (Rahmani et al, 2018), well-being is primarily related to momentary pleasure, enjoyment and positive emotions, i.e.…”
Section: Fandb In the Wellness Experiencementioning
confidence: 99%
“…A viewer-oriented conceptual model which has been guided by the literature review is proposed to illustrate the relationship between webcam travel and psychological well-being (see Figure 1).
Figure 1.Webcam Travel DREAMA Model (Adapted from Filep et al (2022) DREAMA tourist well-being model).
…”
Section: A Conceptual Model Of Webcam Travel and Dreama Psychological...mentioning
confidence: 99%
“…In Jarratt’s study (2021a: 162) webcam travel experiences were found to lead to “a sense of fascination and engagement”. The remaining DREAMA (Filep et al, 2022) dimensions are also generated by the virtual experience, notably affiliation to nature and other people, meaning and achievement. Affiliation with the digital nature has been identified as an important quality of webcam travel experience (Darcy et al, 2022; Jarratt, 2021a).…”
Section: A Conceptual Model Of Webcam Travel and Dreama Psychological...mentioning
confidence: 99%
See 1 more Smart Citation